The burden of severe acute gastroenteritis and risk factors associated with poor outcome in a cohort of Sowetan children under five years of age - Groome, Michelle Jennifer (My University, 2011)
Introduction In developing countries, diarrhoea is a major cause of morbidity and mortality among children under five years of age. This study aimed to determine the effect of age and HIV infection status on incidence of acute gastroenteritis and to identify risk factors associated with death and prolonged hospitalisation. Methods A secondary data analysis was performed using an existing cohort of children enrolled on a pneumococcal vaccine efficacy study performed in 1998-2005 in Soweto. Results The incidence rate of acute gastroenteritis requiring hospitalisation was 10.13 (CI95% 9.68, 10.58) per 1000 person years. Incidence was highest in those under six months of age, decreased with increasing age, and was 5.42 times (CI95% 4.89, 6.01) higher in those infected with HIV compared to that in HIV-uninfected children. HIV-infected children were more likely to be malnourished, have severe dehydration and have a concomitant diagnosis of lower respiratory tract infection (LRTI). HIV-infected children were four times more likely to die in hospital (OR 3.99 CI95% 2.04, 7.81) and almost twice as likely to be hospitalized > 2 days (OR 1.81 CI95% 1.38, 2.38) compared to HIV-uninfected children. Presence of malnutrition, severe dehydration and a concomitant diagnosis of LRTI were also significant risk factors for death and prolonged hospitalisation. Conclusions Acute gastroenteritis is an important cause of hospitalisation in children under 2 years, especially among HIV-infected children. Prevention and management of severe dehydration, malnutrition, HIV infection and concomitant LRTI need to be targeted to decrease mortality and shorten the duration of hospitalisation in children admitted with acute gastroenteritis.
MSc (Med), Epidemiology and Biostatistics,University of the Witwatersrand, Faculty of Health Sciences
Keywords: gastroenteritis; children under 2 years